2019
DOI: 10.1038/s41467-019-12111-x
|View full text |Cite
|
Sign up to set email alerts
|

The fecal resistome of dairy cattle is associated with diet during nursing

Abstract: Antimicrobial resistance is a global public health concern, and livestock play a significant role in selecting for resistance and maintaining such reservoirs. Here we study the succession of dairy cattle resistome during early life using metagenomic sequencing, as well as the relationship between resistome, gut microbiota, and diet. In our dataset, the gut of dairy calves serves as a reservoir of 329 antimicrobial resistance genes (ARGs) presumably conferring resistance to 17 classes of antibiotics, and the ab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

15
153
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(169 citation statements)
references
References 76 publications
15
153
1
Order By: Relevance
“…tetQ and ermB) were present in higher copy numbers than the 16S rRNA gene at the majority of the studied time points. This is consistent with the work of other groups, www.nature.com/scientificreports www.nature.com/scientificreports/ which has demonstrated overall AMR gene abundances of 0.77-5.14 40 and 0.54-3.1 gene copies 41 per 16S rRNA gene in agricultural faecal and wastewater samples. It is worth noting that these AMR gene copy numbers are orders of magnitude higher than in samples obtained from other environments, such as sediments, soil and river water 41,42 .…”
Section: Measured Amr Genes Consistently High Across the Unit Althousupporting
confidence: 92%
“…tetQ and ermB) were present in higher copy numbers than the 16S rRNA gene at the majority of the studied time points. This is consistent with the work of other groups, www.nature.com/scientificreports www.nature.com/scientificreports/ which has demonstrated overall AMR gene abundances of 0.77-5.14 40 and 0.54-3.1 gene copies 41 per 16S rRNA gene in agricultural faecal and wastewater samples. It is worth noting that these AMR gene copy numbers are orders of magnitude higher than in samples obtained from other environments, such as sediments, soil and river water 41,42 .…”
Section: Measured Amr Genes Consistently High Across the Unit Althousupporting
confidence: 92%
“…The effect of the antibiotic treatments was small relative to the longitudinal changes (Additional le 6: Tables S2, S3 and S4), consistent with ndings in pre-weaned dairy calves receiving enro oxacin and tulathromycin metaphylactic treatment [24] and beef cattle receiving oxytetracycline or tulathromycin injection [6]. These ndings can be explained by the existence of a natural resistome, independently of any antibiotic treatment, carried by certain abundant families in the fecal microbiota of pre-weaned calves, as recently shown [28]. Genera of these antibiotic-resistance gene carrying families were found to be dominant in the feces of the veal calves, such as Anaerostipes, Blautia, and Roseburia (Lachnospiraceae family), Enterococcus (Enterococcaceae family), Faecalibacterium and Pseudo avonifractor (Ruminococcaceae family), Bacteroides (Bacteroidaceae family), and Streptococcus (Streptococcaceae).…”
Section: Discussionsupporting
confidence: 87%
“…Moreover, it has been shown that this natural resistome is shaped by the bacterial phylogeny of the fecal microbiome and decreases as the calves age. One of the main drivers of such a decrease was the decrease in abundance of the Enterobacteriaceae family, in which 90% of the members were classi ed as E. coli [28]. It is wellknown that commensal E. coli populations of veal calves harbor high levels of antibiotic-resistance genes [3,29], and that they are diverse.…”
Section: Discussionmentioning
confidence: 99%
“…Consumption of antimicrobials in livestock, as well as antimicrobial residues in food have been proposed to contribute to antimicrobial resistance (AMR) in humans [3,4] and aquatic/soil environments [5,6]. The AMR found in food-producing animals not only reduces the therapeutic e cacy of antimicrobials against diseases but also selects for reservoirs of resistance that could be transferred to humans via the food chain or through the environment [7]. Therefore, reducing antimicrobial resistance and preventing antimicrobial residues from entering the food chain is a priority for livestock industry to address the food safety and public health concerns [8].…”
Section: Introductionmentioning
confidence: 99%
“…It is largely unknown the extent to which ARGs are expressed in the rumen of cattle that are not under the selective pressure antibiotics used in human is unclear. Recent studies have assessed wastewater treatment plant resistome at both metagenomic and metatranscripome levels and reveals that plant locations not only affected the ARGs but also their transcripts [7,17]. However, comparing to largely identi ed resistomes in the animal system, their functionality and activity in vivo has not been reported.…”
Section: Introductionmentioning
confidence: 99%